BS EN ISO 10848-5. Acoustics. Laboratory and field measurement of the flanking transmission for airborne, impact and building service equipment sound between adjoining rooms. Part 5. Radiation efficiencies of building elements (21st October 2019) - British Standards Institution,
No abstract available